Hermeneutika Khaleed M. Abou El-Fadl - Amin, Moh. Nasrul (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
It cannot be denied that the problem of interpretation of religious texts often creates tension. Tensions often occur because each party, both community leaders, religious groups, organizations and fatwa institutions (such as the Permanent Council for specific Research and Legal Opinion (CRLO), Bahsul Masail, Majlis Tarjih, Hisbah Council, MUI Fatwa Commission), Mazhab, and certain religious schools. The fatwas according to Abou El-Fadl are said to be sheltered under the text (nash) which claims that it is actually